The Nexus between the Sleeping Time, Water Consumption and the Body Mass Index - , M. A. D. Priyadarshani, J. A. Weliwita, S. M. M. Lakmali, S. Witharana (Archives of Current Research International, 2018)
Aims: A healthy Body Mass Index (BMI) is widely regarded as important for overall health that helps to avert and control many adverse health effects. It is also known that the sleep deprivation and dehydration have a strong impact on healthy life and sleep deprivation is common among university students and has been associated with poor academic performance. We aim to study the relationship between sleep deprivation and dehydration with BMI. Study Design: Data collection and statistical analysis. Place and Duration of Study: University of Peradeniya, Sri Lanka, between September 2017 and March 2018. Methodology: We examined the association of daily sleeping time and daily water consumption with the Body Mass Index among 452 university students of age 24-26 years and 326 females, and 126 males consented to participate in the study. A cross-tabulation analysis was used to identify the relationship between water consumption and daily sleeping time with BMI. Results: Results of the chi-square test show that there is a significant association between BMI and sleeping time of the students as the calculated chi-square value of 13.771 was significant as p is 0.008 at 4 degrees of freedom. Results of phi and Cramer's V measures of association show that the correlation coefficient between BMI and sleeping time is 0.175 with a p-value of 0.008. Also between BMI and water consumption of the students, the calculated chi-square value of 11.538 was significant as P is 0.021 (<0.05) at 4 degrees of freedom. Results of phi and Cramer's V measures of association show that the correlation coefficient between BMI and water consumption as 0.160 with a p-value of 0.021. Conclusion: The phi measure of symmetric coefficient shows a significant positive association; that is the students who are consuming more water are prone to fall in higher BMI category while students consume less water falls to lower BMI. The phi measure of symmetric coefficient shows a significant positive association; that is the student who gets less sleep are prone to fall in higher BMI category while students take long sleep a day falls to lower BMI.